Keep your magnetics cool in your power supply - Galvan, Glenn (Knovel, 2012)
"Describes a power transformer magnetic in a thermal runaway condition, how a designer can keep his magnetics operating in optimum temperatures and how to predict and mitigate the chance of such defects making into the product."--Knovel